Does there exist an obesity paradox in COVID-19?: insights of the international HOPE-COVID-19-registry - Abumayyaleh, Mohammad S. A.; Núñez Gil, Iván J.; El-Battrawy, Ibrahim; Estrada, Vicente; Becerra-Muñoz, Víctor Manuel; Aparisi, Alvaro; Fernández-Rozas, Inmaculada; Feltes, Gisela; Arroyo-Espliguero, Ramón; Trabattoni, Daniela; López-País, Javier; Pepe, Martino; et al. (Obesity research & clinical practice, 2021)
Background - Obesity has been described as a protective factor in cardiovascular and other diseases being expressed as ‘obesity paradox’. However, the impact of obesity on clinical outcomes including mortality in COVID-19 has been poorly systematically investigated until now. We aimed to compare clinical outcomes among COVID-19 patients divided into three groups according to the body mass index (BMI). - Methods - We retrospectively collected data up to May 31st, 2020. 3635 patients were divided into three groups of BMI (<25 kg/m2; n = 1110, 25−30 kg/m2; n = 1464, and >30 kg/m2; n = 1061). Demographic, in-hospital complications, and predictors for mortality, respiratory insufficiency, and sepsis were analyzed. - Results - The rate of respiratory insufficiency was more recorded in BMI 25−30 kg/m2 as compared to BMI < 25 kg/m2 (22.8% vs. 41.8%; p < 0.001), and in BMI > 30 kg/m2 than BMI < 25 kg/m2, respectively (22.8% vs. 35.4%; p < 0.001). Sepsis was more observed in BMI 25−30 kg/m2 and BMI > 30 kg/m2 as compared to BMI < 25 kg/m2, respectively (25.1% vs. 42.5%; p = 0.02) and (25.1% vs. 32.5%; p = 0.006). The mortality rate was higher in BMI 25−30 kg/m2 and BMI > 30 kg/m2 as compared to BMI < 25 kg/m2, respectively (27.2% vs. 39.2%; p = 0.31) (27.2% vs. 33.5%; p = 0.004). In the Cox multivariate analysis for mortality, BMI < 25 kg/m2 and BMI > 30 kg/m2 did not impact the mortality rate (HR 1.15, 95% CI: 0.889−1.508; p = 0.27) (HR 1.15, 95% CI: 0.893−1.479; p = 0.27). In multivariate logistic regression analyses for respiratory insufficiency and sepsis, BMI < 25 kg/m2 is determined as an independent predictor for reduction of respiratory insufficiency (OR 0.73, 95% CI: 0.538−1.004; p = 0.05). - Conclusions - HOPE COVID-19-Registry revealed no evidence of obesity paradox in patients with COVID-19. However, Obesity was associated with a higher rate of respiratory insufficiency and sepsis but was not determined as an independent predictor for a high mortality.
Gesehen am 23.11.2022